2022
DOI: 10.3390/nano12111870
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Synthesis of Coated Iron Oxide Nanoparticles for Magnetic Hyperthermia

Abstract: Magnetite nanoparticles were synthesized by the co-precipitation method with and without the assistance of an additive, namely, gelatin, agar-agar or pectin, using eco-friendly conditions and materials embodying a green synthesis process. X-ray diffraction and transmission electron microscopy were used to analyze the structure and morphology of the nanoparticles. Magnetic properties were investigated by SQUID magnetometry and 57Fe Mössbauer spectroscopy. The results show that the presence of the additives impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…The outcomes showed that, in terms of phase composition, there are no significant differences among the synthetized MNPs, and the results are in good agreement with the scientific literature [ 75 , 76 , 77 , 78 , 79 ].…”
Section: Discussionsupporting
confidence: 85%
“…The outcomes showed that, in terms of phase composition, there are no significant differences among the synthetized MNPs, and the results are in good agreement with the scientific literature [ 75 , 76 , 77 , 78 , 79 ].…”
Section: Discussionsupporting
confidence: 85%
“…Nanotechnology offers tremendous applications in biomedical engineering for loading therapeutic cures, specifically in cancer treatments. Thanks to their unique surface features, nanoparticles (NPs) can offer a promising platform for loading therapeutic agents in drug delivery systems [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The interaction of NPs with biological systems has offered the simultaneous possibility of targeted drug delivery, monitoring, and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Fe 3 O 4 and γ-Fe 2 O 3 are extensively used in the field of biomedicine due to their paramagnetic/superparamagnetic nature and involvement in various biological processes. Iron oxide magnetic nanoparticles (IOMNPs) provide a theranostic platform where they can be exploited for diagnostic purposes, such as magnetic resonance imaging (MRI), and therapeutic purpose, such as drug delivery, magnetic cell separation, protein purification and bio-catalysts [ 101 , 102 , 103 ]. IOMNPs can be synthesised in different sizes and shapes using a variety of synthesis methods.…”
Section: Iron Oxide Nanostructuresmentioning
confidence: 99%